Metodologi Pengajaran PAI dengan Metode Pembelajaran Konvensional di Madrasah Tsanawiyah Negeri 3 Kabupaten Batang Hari - Asmadi, Asmadi; Faridah, Farah; Sakdiah, Nur; Sa’diyah, Shella Ainun; Yuranti, Lisa; Tari, Najwa Rahmanda (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study explores the teaching of Islamic Religious Education (PAI) at MTs Negeri 3 Batang Hari Regency, where the conventional teacher-centered learning method remains the predominant approach. The research employs a descriptive-qualitative methodology, collecting data through observations, interviews, and document analysis. The findings indicate that while conventional methods are effective in delivering theoretical content, they lack the ability to engage students interactively and fail to address diverse learning needs fully. To enhance the quality of PAI instruction, integrating innovative and engaging learning media is recommended, alongside continuous teacher training in pedagogical and technological skills. These strategies can create a more interactive and relevant learning environment that positively impacts students’ academic success and character development. Furthermore, this research highlights the importance of adopting adaptive and innovative teaching approaches to ensure that PAI teaching aligns with the evolving demands of modern education while enriching students' overall learning experiences.